2011
DOI: 10.1124/jpet.111.179358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Treatment with Phosphodiesterase-4 Inhibitors on cAMP Signaling, Hippocampal Cell Proliferation, and Behavior in the Forced-Swim Test

Abstract: The effects of repeated treatment with the phosphodiesterase-4 (PDE4) inhibitors rolipram, piclamilast, and 4-(2-(3-(cyclopentyloxy)-4-methoxyphenyl)-2-phenylethyl)pyridine (CDP840), which differ in their interactions with high-and low-affinity binding conformers of the enzyme, were contrasted to those of acute treatment on cAMP signaling, hippocampal cell proliferation, and immobility in the forced-swim test in rats. Repeated treatment with rolipram (1 and 3 mg/kg), piclamilast (0.3 and 1 mg/kg), or CDP840 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Then, pharmacological modulation of the Ca 2+ /cAMP signalling interaction could be a new therapeutic strategy to treat neurological and psychiatric disorders resulting from neurotransmitter release deficit. In addition, pharmacological modulation of the Ca 2+ /cAMP signalling interaction could reduce neuronal death in neurodegenerative disease due to attenuation of cytosolic Ca 2+ overload, increase of [cAMP]c and stimulation of cell survival pathways mediated by CREB [22][23][24]. Thus, pharmacological modulation of Ca 2+ /cAMP signalling interaction could be a new neuroprotective therapeutic strategy to slow the progression of neurodegenerative diseases, such as AD [5][6][7][8]25,26].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Then, pharmacological modulation of the Ca 2+ /cAMP signalling interaction could be a new therapeutic strategy to treat neurological and psychiatric disorders resulting from neurotransmitter release deficit. In addition, pharmacological modulation of the Ca 2+ /cAMP signalling interaction could reduce neuronal death in neurodegenerative disease due to attenuation of cytosolic Ca 2+ overload, increase of [cAMP]c and stimulation of cell survival pathways mediated by CREB [22][23][24]. Thus, pharmacological modulation of Ca 2+ /cAMP signalling interaction could be a new neuroprotective therapeutic strategy to slow the progression of neurodegenerative diseases, such as AD [5][6][7][8]25,26].…”
Section: +mentioning
confidence: 99%
“…/cAMP signalling interaction regulates various cellular responses, including neurotransmitter release [5][6][7][8]. Many studies showed that increase of [cAMP]c stimulates neuroprotective response attenuating neuronal death due probably to activation of cellular survival pathways mediated by cAMP-response element binding protein (CREB) [22][23][24]. In this way, pharmacological modulation of the Ca 2+ /cAMP signalling interaction by combined use of L-type CCBs and cAMP-enhancer compounds could stimulate neuroprotective response due to increase of [cAMP]c and attenuation of cytosolic Ca 2+ overload [5][6][7][8].…”
Section: + /Camp Signalling Interaction In Neuroprotectionmentioning
confidence: 99%
“…Indeed, many reports have shown that increase of cytosolic cAMP concentration ([cAMP]c) stimulates neuroprotective effects [13,14]. Thus, elevating [cAMP]c by handling Ca 2+ /cAMP signalling interaction could reduce neuronal death triggered by cytosolic Ca 2+ overload [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have showed that chronic treatment with rolipram, together with typical antidepressants has been successful in the reduction of depression symptoms due to potentiation of these antidepressants effects [26]. Considering our model in which increment of [cAMP]c stimulates Ca 2+ release from ER (Figure 1), it may be plausible that the therapeutic use of the PDE inhibitor rolipram [27,28], in combination with low doses of verapamil to potentiate neurotransmission (Figure 1) in the areas of central nervous system involved in neurological/psychiatric disorders in which neurotransmission is reduced, including depression. This new pharmacological strategy for the treatment of psychiatric disorders could increase the therapeutic ef icacy and reduce the adverse effects of the medicines currently used for treating depression.…”
Section: Paradoxical Effects Of Ccbs and Their Pleiotropic Effects Inmentioning
confidence: 99%